2006
DOI: 10.1074/jbc.m605186200
|View full text |Cite
|
Sign up to set email alerts
|

An Allosteric Activator of Glucokinase Impairs the Interaction of Glucokinase and Glucokinase Regulatory Protein and Regulates Glucose Metabolism

Abstract: Glucokinase (GK) plays a key role in the control of blood glucose homeostasis. We identified a small molecule GK activator, compound A, that increased the glucose affinity and maximal velocity (V max ) of GK. Compound A augmented insulin secretion from isolated rat islets and enhanced glucose utilization in primary cultured rat hepatocytes. In rat oral glucose tolerance tests, orally administrated compound A lowered plasma glucose elevation with a concomitant increase in plasma insulin and hepatic glycogen. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
78
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 25 publications
6
78
0
Order By: Relevance
“…S6). This result indicates that GKA dissociates GKRP (7,9,17,23) through a structural rearrangement of GK.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…S6). This result indicates that GKA dissociates GKRP (7,9,17,23) through a structural rearrangement of GK.…”
Section: Resultsmentioning
confidence: 85%
“…It is noteworthy that F1P is likely to be more efficient than glucose or GKA in releasing GK from GKRP. Although F1P, glucose, and GKA bind to distant sites from the interface of the GK/GKRP complex (9), F1P induces direct disruption of the interface to release GK from GKRP, whereas glucose and GKA induce slow and energetically unfavorable rearrangement of the GK small domain (9,17). The superimposition of F6P-bound hGKRP onto apohGKRP revealed that the interaction between the hydroxyl group of C1 in F6P and Glu348 of α10 in SIS domain 2 shifts α10 downward (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the report by Grimsby et al in 2003 [5], several glucokinase activators (GKAs) have been developed, and these have been shown to lower blood glucose in several animal models of type 2 diabetes [5][6][7][8][9][10][11][12]. In a study of beta cell function, it was reported that a GKA stimulated insulin secretion in a Ca 2+ -dependent manner in rodent islets and MIN6 cells [13], and we and others have reported that GKAs promoted beta cell proliferation and increased production of IRS2 [11,14], which is critically required for beta cell growth and survival [3,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…GKAs have demonstrated prominent antihyperglycaemic activity in animal models [12][13][14][15] and in clinical trials [16,17]. It is, however, currently uncertain whether long-term improvements in glycaemic control can be achieved with these agents.…”
Section: Introductionmentioning
confidence: 99%